(untitled) (Ciencias Veterinarias, 2024)
Carnivore protoparvovirus 1 (CPPV-1) includes feline parvovirus (or feline panleukopenia virus, FPV) and canine parvovirus 2 (CPV-2). Currently, although CPV-2 is not found in nature, its variants CPV-2a, CPV-2b, and CPV-2c are found and can infect cats as well. The objective of this research was to identify CPPV-1 and its variants as antibodies against CPPV-1 in the blood of domestic cats from the Central Valley of Costa Rica. Blood samples were collected from 155 cats, along with the following data: sex, age, breed, vaccination information, the environment where the animal lives (urban or rural), coexistence with other cats, health status, any chronic diseases, lifestyle (indoor or outdoor cat), and place of origin. Blood samples were analyzed by hemagglutination inhibition assay (HIA) and molecular techniques (polymerase chain reaction (PCR) and sequencing). Antibodies against CPPV-1 were detected using HIA in all cats; a total of 112 (72.3%) had protective titers (≥1:80). Using real-time PCR, CPPV-1 was detected in the blood of 42 (27.1%) cats, none of which presented anemia, leukopenia, or any chronic disease; five (11.9%) were vaccinated, and three (7.1%) had low body condition but showed appetite and had no other symptom or sign associated with CPPV-1. The group of qPCR-positive cats did not show significant differences compared to the qPCR-negative group regarding age, sex, lifestyle, coexistence with other cats, and antibody titers. Ten asymptomatic and healthy cats showed FPV (n=2) and CPV-2c (n=8) in blood with nucleotide similarities of 100% (GenBank M38246) and 99.8%-100% (GenBank AF401519), respectively.